Numerical prediction of trailing edge noise at low Reynolds number with modified trailing edges of a NACA 0015 airfoil - Hassan, Mohamed Ibren (Semarak Ilmu Publishing, 2024)
Global concern about high noise levels in areas near airports and wind farms has generated interest from various groups due to factors such as potential health problems and dissatisfaction among the local community. To accommodate this worthwhile plan of further reducing overall noise levels, some researchers are working on lowering the contribution of trailing-edge noise. The original scientific contribution of this study lies on understanding the efficiency of various trailing edge designs such as baseline, serrations, comb and comb-serrated, across different angles of attack and Reynolds numbers, while also addressing the limitations of existing geometrical models for trailing edges. The study intends to examine the performance of these different configurations, with an emphasis on their effect on acoustic responses. By utilizing large-eddy simulation and applying the Ffowcs-Williams and Hawkings models for noise prediction, an investigation was conducted to assess the impact of these trailing edge configurations on radiated noise at a low Reynolds number of 1.6× 105. The numerical predictions of lift coefficient and surface pressure fluctuations are compared and validated with a published study and experimental data, showing satisfactory results. Further analysis of these study has demonstrated that prominent peaks at lower frequencies (<103) are observed, which are identified as the characteristic frequencies. Moreover, results showed irregular broadband noise (300 - 600 Hz) with increased noise and shifting peak frequency as angle of attack rose. The serrated trailing edge design notably reduced noise levels by roughly 21 dB, especially for low frequencies. Comb-serration increased high-frequency noise by about 9 dB for angles of attack at 0, -1, and -20, and achieved a reduction of approximately 9 dB for angles of attack at 1 and 20. On the other hand, the directivity pattern showed that the maximum noise level is observed to predominantly radiate at an azimuth angle of around 90 degrees for all the cases, ranging from 900 to 2700, indicating that the majority of the source's acoustic energy is being emitted on the suction and pressure sides of the airfoil.